Investigation of industrial tea-leaf-fibre waste material for its sound absorption properties - KÜÇÜK, HALUK; ERSOY, SEZGİN (ELSEVIER SCI LTD, 2009)
The sound absorption of an industrial waste, developed during the processing of tea leaves has been investigated. Three different layers of tea-leaf-fibre waste materials with and without backing provided by a single layer of woven textile cloth were tested for their sound absorption properties. The experimental data indicate that a 1cm thick tea-leaf-fibre waste material with backing, provides sound absorption which is almost equivalent to that provided by six layers of woven textile cloth. Twenty millimeters thick layers of rigidly backed tea-leaf-fibres and non-woven fibre materials exhibit almost equivalent sound absorption in the frequency range between 500 and 3200 Hz. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Sound absorption; Tea-leaves; Fibre; Insulation; COMPOSITE